Handbook of chemical vapor deposition principles, technology, and applications - Pierson, Hugh O. (Noyes Publications, 1999)
CVD technology has grown at a rapid rate, and the number and scope of its applications and their impact on the market have increased considerably. The market is now estimated to be at least double that of a mere seven years ago when the first edition of this book was published. The second edition is an update with a considerably expanded and revised scope. Readers will find data on both Plasma CVD and metallo-organic CVD processes. The book also explains the growing importance of CVD in production of semiconductor and related applications.
Keywords: Vapor-plating -- Handbooks, manuals, etc.; Chemical vapor deposition -- Handbooks, manuals, etc.; elektronické knihy; electronic books